Pancreatic beta cell ER export in health and diabetes - Barrabi, Cesar; Zhang, Kezhong; Liu, Ming; Chen, Xuequn (Frontiers in Endocrinology, 2023)
In the secretory pathway of the pancreatic beta cell, proinsulin and other secretory granule proteins are first produced in the endoplasmic reticulum (ER). Beta cell ER homeostasis is vital for normal beta cell functions and is maintained by the delicate balance between protein synthesis, folding, export and degradation. Disruption of ER homeostasis leads to beta cell death and diabetes. Among the four components to maintain ER homeostasis, the role of ER export in insulin biogenesis or beta cell survival was not well-understood. COPII (coat protein complex II) dependent transport is a conserved mechanism for most cargo proteins to exit ER and transport to Golgi apparatus. Emerging evidence began to reveal a critical role of COPII-dependent ER export in beta cells. In this review, we will first discuss the basic components of the COPII transport machinery, the regulation of cargo entry and COPII coat assembly in mammalian cells, and the general concept of receptor-mediated cargo sorting in COPII vesicles. On the basis of these general discussions, the current knowledge and recent developments specific to the beta cell COPII dependent ER export are summarized under normal and diabetic conditions.